Profiling the Prognosis of Gastric Cancer Patients: Is It Worth Correlating the Survival with the Clinical/Pathological and Molecular Features of Gastric Cancers? - Laura Lorenzon; Paolo Mercantini; Mario Ferri; Marco La Torre; Alessandra Sparagna; Genoveffa Balducci; Giulia Tarantino; Adriana Romiti; Emanuela Pilozzi; Vincenzo Ziparo (The Scientific World Journal)
Background. The prognosis of gastric cancer patients still remains poor. The aim of this study was investigating the prognostic value of several clinical/pathological/molecular features in a consecutive series of gastric cancers. Methods. 150 R0 gastrectomies plus 77 gastric cancer patients evaluated for the HER2 overexpression were selected. Survival was calculated and patients stratified according to the stage, the T-stage, the LNRs, the LNH, and the HER2 scoring system. ROC curves were calculated in order to compare the performance of the LRN and LNH systems. Results. Prognosis correlated with the stage and with the T-stage. We documented a statistical correlation between the LNRs and the survival. Conversely, a LNH > 15 did not correlate with the outcomes. The ROC curves documented a significant performance of the LRN system, whereas a statistical correlation was documented for the LNH exclusively with the endpoint of disease-free survival. We documented a trend of worse prognosis for patients with an HER2 overexpression, even though it was not of statistical value. Conclusion. The LNR and the evaluation of the HER2 overexpression might be useful since they correlate with survival, might identify patients with a higher risk of recurrence, and might select patients for a tailored medical treatment.